The Development of Tempeh Packaging Mechanism Prototype: Slicer Folded and Binding Part to Pack Tempeh by using Kraft Paper - Aida Amira binti Azman, (Progress in Engineering Application and Technology, 2023)
This project is the development of Automated Tempeh Packaging Machine. The objective of this project is to develop a prototype of tempeh packaging machine. The scope of this project is focusing on the packaging process by using kraft paper. The development of this packaging machine consists of paper folding and banding part that was designed using Solidworks software. To build the prototype of this machine, there are many manufacturing process conducted, which are welding process, lathe machining process, cutting process, drilling process, bending process, and rapid prototyping process. There is two type of packaging process which is manual and automated. For this automated tempeh packaging machine, the design consists of four stages which is paper supply, soybean feeder, paper folding and banding part. Therefore, for this project only focusing on the paper folding and banding process. This banding process of the machine consist of two part which is rubber band supplier and banding part. The mechanisms that will control the movement of the machine are DC motor servo motor and Arduino. The objectives of this project are successfully achieved. The prototype was successfully design and fabricate. The mechanism of this prototype is 60% functional. However, this prototype needs more improvement.